2020
DOI: 10.1155/2020/2148562
|View full text |Cite
|
Sign up to set email alerts
|

Sulfiredoxin as a Potential Therapeutic Target for Advanced and Metastatic Prostate Cancer

Abstract: The incidence of prostate cancer (PCa) is increasing, and it is currently the second most frequent cause of death by cancer in men. Despite advancements in cancer therapies, new therapeutic approaches are still needed for treatment-refractory advanced metastatic PCa. Cross-species analysis presents a robust strategy for the discovery of new potential therapeutic targets. This strategy involves the integration of genomic data from genetically engineered mouse models (GEMMs) and human PCa datasets. Considering t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 90 publications
(105 reference statements)
1
13
0
Order By: Relevance
“…On the other hand, by reducing ROS and affecting apoptosis, Srx may favor the survival of cancerous cells and thereby contribute to carcinogenesis [ 48 ]. For instance, Srx underexpression can sensitize cancer cells to ER stress-induced cell death [ 49 ], increase apoptosis of tumor cells and thus decrease tumor cell proliferation, while the opposite effects have been observed in Srx overexpressors, which correlated with more aggressive cancers and poor prognosis [ 8 , 48 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, by reducing ROS and affecting apoptosis, Srx may favor the survival of cancerous cells and thereby contribute to carcinogenesis [ 48 ]. For instance, Srx underexpression can sensitize cancer cells to ER stress-induced cell death [ 49 ], increase apoptosis of tumor cells and thus decrease tumor cell proliferation, while the opposite effects have been observed in Srx overexpressors, which correlated with more aggressive cancers and poor prognosis [ 8 , 48 , 50 , 51 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…16 It had been demonstrated as a critical player in cell proliferation, migration, and metastasis, 6 and its abnormal expression usually contributed to the poor survival. 15,[17][18][19] All these evidence revealed that SRXN1 functioned as an oncogene. Study had demonstrated SRXN1 and peroxiredoxin 1 (RRDX1) played a pivotal role in protecting the liver in ethanol-fed mice against oxidative injury by eliminating ROS.…”
Section: Introductionmentioning
confidence: 89%
“…Studies had shown that SRXN1 was overexpressed in multiple types of malignancies, including cervical cancer, 12 colorectal cancer, 13 skin cancer, 14 lung cancer, 15 and renal cell carcinoma 16 . It had been demonstrated as a critical player in cell proliferation, migration, and metastasis, 6 and its abnormal expression usually contributed to the poor survival 15,17‐19 …”
Section: Introductionmentioning
confidence: 99%
“…Overoxidation of the peroxidatic cysteine yields sulfinic or irreversible sulfonic acid, rendering PRDX inactive [206] ( Figure 2). Sulfinic acid in PRDX can be reduced to sulfenic acid by sulfiredoxin, an antioxidative enzyme that is explored as a potential drug target in cancer therapy [207][208][209]. Reversible sulfenic acid in PRDXs is reduced by the thiol-containing thioredoxin, which exists as a cytosolic (TXN1) and a mitochondrial version (TXN2).…”
Section: The Peroxiredoxin-thioredoxin Systemmentioning
confidence: 99%